Clinical Characteristics and Management Outcomes of Rhegmatogenous Retinal Detachments Due to Retinal Dialysis. (September 2021) - Mahmoudzadeh, Raziyeh; Huang, Denis; Salabati, Mirataollah; Awh, Katherine; Garg, Sunir; Hsu, Jason; Ho, Allen; Regillo, Carl
Purpose: This work assesses the clinical characteristics and outcomes of various treatment methods in managing rhegmatogenous retinal detachments secondary to retinal dialysis. Methods: In this retrospective, consecutive case series, patients presenting to a tertiary referral vitreoretinal service from 2015 to 2020 were chosen. The primary outcome measure was the single-surgery anatomic success (SSAS) rate in the first 90 days after surgery and overall SSAS rate until the last visit. Results: Eighty-six eyes of 84 patients were included. Mean (SD) age was 30 (14.8) years (range, 7-71 years). Fifty-nine (70%) patients were men and 55 eyes (64%) had a history of trauma. Dialysis occurred in the inferotemporal quadrant in 50 eyes (58%) of the entire cohort and 25 of 55 eyes (45%) with prior trauma. Fifty-one eyes (59.3%) were managed by scleral buckle (SB), 25 eyes (29.2%) with laser retinopexy, and 10 eyes (11.6%) with pars plana vitrectomy (PPV). The SSAS rate in the first 90 days after surgery was 94.1% (81 of 86 eyes), including 90.1% of eyes with SB, 100% of eyes with laser retinopexy, and 100% of eyes with PPV ( P = .07). The overall SSAS rate, however, was 89.5% (77 of 86) eyes, including 90.1% of eyes with SB, 84% of eyes with laser retinopexy, and 100% of eyes with PPV ( P = .4). Final attachment rate was 100% in the entire cohort. Conclusions: With careful consideration of underlying pathology, all 3 treatment modalities can provide high rates of anatomic and functional success.